Pedagogy in creative disciplines: considerations for learning space design - Flintoff, Kim; Martin, Romana; Barker, Alison; Broadley, Tania (2016)
The importance of creativity as an attribute of the 21st Century learner is now widely acknowledged and a global trend across all disciplines. To meet both current and future needs of both students and society a university education must develop and support creativity in learners. This paper was developed to outline the range of creative disciplines, the diversity and interconnectedness of the disciplines, and how this is reflected in the needs for appropriate pedagogical models and consequently spaces for learning, both formal and informal.